Exploring the Linguistic Landscape of Kuching Waterfront to Enhance Arab Tourist Experience: Opportunities and Challenges - Mohd Azhar, Ali; Mohd Sham, Kamis; Roslan, Ali; Yahya, Bakeri; Sandra Ying Khoo, Ying (Knowledge Words Publications, 2025)
This study investigates the potential of Arabic as a tourism language in Kuching Waterfront, Sarawak, Malaysia. Employing a mixed-methods approach, the research examined the current linguistic landscape, including signage, advertisements, and tourist information materials. Findings revealed a significant lack of Arabic language presence, including limited Arabiclanguage information, insufficient Arabic-speaking staff, and an absence of dedicated Arabiclanguage tourism packages. A total of 149 valid responses were analysed and the results indicated that language visibility and language comprehensibility play a significant role on tourist satisfaction. This study emphasizes the need for strategic initiatives to integrate Arabic into the tourism sector, such as developing Arabic-language tourism packages, providing language training, raising community awareness, and enhancing the visibility of Arabic language in the tourism landscape. By addressing these issues, Kuching Waterfront can effectively attract Arabic-speaking tourists and enhance its competitiveness in the global tourism market.